ETIKA BERBAGI NASI DI MASYARAKAT BANDUNG SERTA ANALISIS TERHADAP KONSEP DAN DAMPAK SOSIAL - Danang Nugroho; Giyasi Nur Sabila; Dalfa Rubi Nurfadilah; Della Aprilia; Dwi Sulistia Ningrum (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This article discusses the ethics of sharing rice in Bandung society and analyzes the concept and related social impacts. This research aims to understand the practice of sharing rice in Bandung society, analyze the ethical concepts underlying this practice, and evaluate the resulting social impact. The research method used is a qualitative study. Qualitative research aims to understand the experiences of research subjects, such as their actions, cognition, motivation and behavior, as a whole through descriptions in the form of words and language in certain natural contexts. natural ways and by utilizing various methods natural. by collecting data through participant observation, interviews and document analysis (Anwar Hidayat & Tim, 012). The theoretical description involves a review of the literature on social ethics, social solidarity, and food sharing practices. The discussion of this article will describe the research findings and analyze the social implications of the practice of sharing rice in Bandung society. Conclusions and suggestions will provide a summary of research findings and recommendations for developing more effective and sustainable rice sharing practices in Bandung society.